Internalization of Pancasila Values in Formulating Sustainable Village Regulations - Umam, Khairul; Fallahiyan, Muh.; Kafrawi, Rachman (Research Horizon, 2023)
This study aims to ascertain whether the formulation of village regulations in the Pringgasela Sub-district has internalized Pancasila values during the process of regulation-making. Additionally, this research examines the strategic steps undertaken to internalize Pancasila values into village regulations within the Pringgasela Sub-district. This study adopts a normative research approach that employs the statutory approach, conceptual approach, and sociological approach. The findings reveal that the formulation of village regulations in the Pringgasela Sub-district has not fully addressed the legal needs of the local community. These regulations have not been developed using appropriate methodologies and techniques aligned with Pancasila values. Meanwhile, to internalize Pancasila values in the formulation of village regulations in the Pringgasela Sub-district, several strategies are employed. These strategies include education and awareness of Pancasila values, community participation in village regulation formation, integration of Pancasila values into village regulation texts, oversight and law enforcement, collaboration and synergy with relevant institutions, training and capacity building of village officials, development of Pancasila-based programs and activities, and ongoing evaluation and improvement of village regulations.